Differences in Clinical Simulation with Audiovisual and Practicum-based Standard Operating Procedures in Nursing Student Competencies - Hendri Palupi; Kusnanto Kusnanto; Slamet Riyadi Yuwono (Jurnal Ners, 2019)
Introduction: The biggest challenge in nursing education is to produce nurses who are professional and competent. Effective and efficient learning through appropriate methods and media is very important. Practical learning based on standard operating procedures (SOP) has been widely applied, but clinical simulation approaches with audio-visual media have not been scientifically proven. The purpose of this study is to compare student competencies through clinical simulation learning with audio-visual media and practicums based on SOP.Methods: This was a quasi-experimental study with a pretest-posttest control group design. The sample consisted of 40 students recruited using simple random sampling and then divided into 2 groups: 20 respondents were given clinical simulation methods using audio-visual materials and 20 respondents were given practicum based on SOP. The independent variables were clinical simulation with audio-visual media and practicum based on standard operating procedures. The dependent variable was student competency, assessed using competency assessment including cognitive, affective, and psychomotor methods. Data analysis was conducted using the Wilcoxon test.Results: The use of clinical simulations with audio-visual media and practicum based on SOP can increase the value of competency in nursing students, but the median value on the use of clinical simulations using audio-visual sources is higher than practicum based on SOP.Conclusion: Clinical simulations with audio-visual media can be recommended as effective learning methods and media for nursing students.